2016
DOI: 10.1002/ange.201510443
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer Stem Cell Potent Copper(II)–Non‐Steroidal Anti‐Inflammatory Drug Complexes

Abstract: The breast cancer stem cell (CSC) potency of aseries of copper(II)-phenanthroline complexes containing the nonsteroidal anti-inflammatory drug (NSAID), indomethacin, is reported. The most effective copper(II) complex in this series, 4,s electivity kills breast CSC-enriched HMLER-shEcad cells over breast CSC-depleted HMLER cells.F urthermore, 4 reduces the formation, size,a nd viability of mammospheres, to ag reater extent than salinomycin, ap otassium ionophore knowntoselectively inhibit CSCs.Mechanistic studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 46 publications
(22 citation statements)
references
References 48 publications
0
22
0
Order By: Relevance
“…For this scope, we decided to study the complexes alone or conjugated to the nonsteroidal anti‐inflammatory drug (NSAID) indomethacin. This chemical design was inspired by the fact that molecular units comprising a metal fragment and NSAID have been previously reported to enhance anticancer properties . Remarkably, it was found that the rhenium complexes were active against pancreatic cell lines, whereas the ruthenium complexes did not show any significant activity.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…For this scope, we decided to study the complexes alone or conjugated to the nonsteroidal anti‐inflammatory drug (NSAID) indomethacin. This chemical design was inspired by the fact that molecular units comprising a metal fragment and NSAID have been previously reported to enhance anticancer properties . Remarkably, it was found that the rhenium complexes were active against pancreatic cell lines, whereas the ruthenium complexes did not show any significant activity.…”
Section: Figurementioning
confidence: 99%
“…This chemicald esign wasi nspired by the fact that molecular units comprising am etal fragment and NSAID have been previously reported to enhancea nticancerp roperties. [20][21][22][23][24][25][26] Remarkably,i t was found that the rhenium complexes were active against pancreatic cell lines, whereas the ruthenium complexes did not show any significant activity.F urthermore,c onjugation to indomethacin did not seem to enhancet he anticancer activity, which was traced back exclusively to the presence of the Re(CO) 3 fragment. With this study,f or the first time, it was possible to elucidate that the anticancer properties of the rhenium tricarbonyl fragment originatef rom the labilityo ft he monodentate ancillary ligand coordinated to the rheniumc enter by inducing G2/M cell cyclea rrest and blockade of Aurora-A kinase phosphorylation.…”
mentioning
confidence: 99%
“…Therefore, copper can be considered an alternative to other metal-based drugs, particularly those with platinum compounds, which have many side effects, such as neurotoxicity, ototoxicity, emetogenesis, nephrotoxicity, fatigue, petechial, alopecia, diarrhoea, anaemia [1,9,10]. Currently, copper gluconate complex co-administered with disulfiram is subject to clinical research in therapy for refractory solid malignancies [8,11]. However, the main problem in the use of copper in anti-cancer therapy is its poor water-solubility, which can significantly reduce the bioavailability of copper-based drugs [12].…”
Section: Introductionmentioning
confidence: 99%
“…Coordination of NSAIDs to metal centers aims at obtaining antiproliferative activity through a dual mode of action: inhibition of COX and, e.g., ROS generation by the metal. Complexes of Ru II , Os II , Cu II , Re II , Fe II , Co II and Zn II with indomethacin, naproxen, diclofenac and ibuprofen have been reported [3][4][5][6][7][8][9][10][11]. Examples of ASA derivatives involve Ir III [12], Pt IV [13], Ag I [14,15] and various metal carbonyls [16][17][18].…”
Section: Introductionmentioning
confidence: 99%